Pengaruh Aset Pajak Tangguhan dan Earning Power Terhadap Praktik Manajemen Laba Perusahaan BUMN Pada Sektor Perbankan di BEI Tahun 2020-2022 - Lestari, Dewi Dwi Puji; Sodik, M.; Hasan, Khojanah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study aims to examine the effect of deferred tax assets and earning power on earnings management practices in state-owned banking companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2022. Earnings management refers to actions taken by company management to influence financial statements for specific purposes. Deferred tax assets and earning power are suspected to be two factors that may influence a company's tendency to engage in such practices. This research uses a quantitative approach with a causal associative type of study. The population consists of all state-owned banking companies listed on the IDX, with a census method applied to four companies: PT. Bank Negara Indonesia Tbk. (BBNI), PT. Bank Rakyat Indonesia Tbk. (BBRI), PT. Bank Tabungan Negara Tbk. (BBTN), and PT. Bank Mandiri Tbk. (BMRI). The data analysis technique employed is multiple linear regression. The results show that partially, deferred tax assets do not have a significant effect on earnings management, while earning power has a significant effect. Simultaneously, deferred tax assets and earning power significantly affect earnings management practices. These findings are expected to contribute to the development of accounting science and serve as a reference for company management and stakeholders in making decisions based on financial reports.